Resolution of Social Conflicts Between Fishermen Through a Collaborative Approach - K, Ernawati S. (Universitas Negeri Makassar, 2024)
The purpose of the research study is to describe and analyze efforts to resolve fishermen's social conflicts through the collaboration of the government and the community in the Togean Islands, Tojo Una-una Regency. This research is a descriptive-qualitative research. The research informants were selected deliberately with certain criteria, namely from the local government, the community, and fishermen. Data collection uses observation, interview, and documentation methods. Then the data was analyzed using descriptive-qualitative analysis. The output of the research is that the resolution of fishermen's social conflicts is carried out in the form of the involvement of the Togean Islands regional government by forming a special community of marine guards, empowering fishermen, and providing assistance to fishermen. Meanwhile, the form of community involvement of villages in the Togean Islands is to be active members of the community, such as becoming a marine guard established by the government, participating in patrols with special marine guard communities. Then efforts to resolve fishermen's social conflicts through the collaboration of the government and the community are carried out through avoidance, competition, compromise, and accommodation.